Seasonality of nutrients vis-à-vis fruit quality of pomegranate cv. Bhagwa on vertisol. (28th May 2017) - Maity, Ashis; Babu, Karuppnan Dinesh; Sarkar, Ananta; Pal, Ram Krishna
ABSTRACT: The temporal changes of nutrient concentration in leaves and their accumulation in fruit are good indicators of plant nutrient demand for each developmental stage. Seasonality of nutrients in leaves and fruits of pomegranate and their relation with fruit quality was evaluated in commercial orchards using cv. "Bhagwa." The concentration of nitrogen (N), phosphorus (P), potassium (K), sulfur (S), iron (Fe), zinc (Zn) and boron (B) in leaves decreased while calcium (Ca), magnesium (Mg), manganese (Mn) and copper (Cu) concentration increased during fruit growth and development. Total nutrient accumulation increased gradually in fruit and translated into growth of arils, and increase in juice content and total soluble solids, however as the biomass accumulation in fruit was much faster than nutrient accumulation, concentration of majority nutrients except Mg decreased rapidly, followed by slow and continuous decrease till maturity. During fruit enlargement, demand for N, P, K, Fe, Cu and Zn was high while requirement for Ca, Mg and S was high during fruit development.